PENGARUH MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN CV. BONANZA - Pindo Asti; Didik Sofian Haryadi; Afif Nala Niam (MANAJEMEN, 2021)
The progress of an organization can be seen from the performance of its employees which can be triggered by work motivation and a good organizational culture. The research conducted by the author tries to understand and analyze how much influence work motivation and organizational culture have in improving employee performance. The research was conducted at CV. Bonanza in Boyolali district with multiple linear regression analysis method with the help of SPSS 23.0 software. The sampling technique used was saturated sampling, where the entire population was sampled as many as 30 respondents. The results show that the variables of work motivation and organizational culture have a positive and significant influence on employee performance. The work motivation variable has a very dominant influence as evidenced by the largest t-value with a value of 4.330.